2023
DOI: 10.1177/14791641231173630
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of coronary microvascular function by OGA overexpression in a high-fat diet with low-dose streptozotocin-induced type 2 diabetic mice

Abstract: Sustained hyperglycemia results in excess protein O-GlcNAcylation, leading to vascular complications in diabetes. This study aims to investigate the role of O-GlcNAcylation in the progression of coronary microvascular disease (CMD) in inducible type 2 diabetic (T2D) mice generated by a high-fat diet with a single injection of low-dose streptozotocin. Inducible T2D mice exhibited an increase in protein O-GlcNAcylation in cardiac endothelial cells (CECs) and decreases in coronary flow velocity reserve (CFVR, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Mice with type 2 diabetes (T2D) exhibit an increase in the protein O-GlcNAcylation of cardiac endothelial cells. OGA overexpression in endothelial cells significantly reduced O-GlcNAcylation in cardiac endothelial cells, increased the CFVR and capillary density and reduced endothelial cell apoptosis in mice with T2D [72]. A study showed that rat cardiac fibroblasts cultured in high-glucose conditions had increased overall protein O-GlcNAcylation.…”
Section: Diabetic Cardiomyopathymentioning
confidence: 99%
See 2 more Smart Citations
“…Mice with type 2 diabetes (T2D) exhibit an increase in the protein O-GlcNAcylation of cardiac endothelial cells. OGA overexpression in endothelial cells significantly reduced O-GlcNAcylation in cardiac endothelial cells, increased the CFVR and capillary density and reduced endothelial cell apoptosis in mice with T2D [72]. A study showed that rat cardiac fibroblasts cultured in high-glucose conditions had increased overall protein O-GlcNAcylation.…”
Section: Diabetic Cardiomyopathymentioning
confidence: 99%
“…Mitochondrial protein O-GlcNAcylation plays an important role in regulating cellular function; the destruction of O-GlcNAcylation homeostasis is involved in the pathogenesis of chronic diseases such as diabetes [43,72,73], neurodegenerative diseases [74,75], tumors [28,76,77] and CVDs [14,26,44]. Insulin resistance and diabetic CVDs are promoted by O-GlcNAcylation through an increase in the imbalance of multiple signaling pathways at the transcriptional, translational and posttranslational levels.…”
Section: The Regulatory Mechanisms Of Protein O-glcnacylation On Mito...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in diverse forms of cardiac injury, OGT hyperexpression promotes cardiac fibrosis and maladaptive remodelling, which is rescued by hyperexpression of OGA 45,149,150 . O‐GlcNAcylation stimulates collagen synthesis by cardiac fibroblasts, 151 and impairs nitric oxide synthase in endothelial cells and impairs microvascular dysfunction 152,153 . Hexokinase‐1 bound to mitochondria drives cardiac endothelial inflammation, a hallmark of heart failure and a preserved ejection fraction, and this heart failure phenotype is reportedly alleviated by inhibition of O‐GlcNAcylation 154 .…”
Section: O‐glcnacylation In the Injured Stressed And Failing Heartmentioning
confidence: 99%
“…45,149,150 O-GlcNAcylation stimulates collagen synthesis by cardiac fibroblasts, 151 and impairs nitric oxide synthase in endothelial cells and impairs microvascular dysfunction. 152,153 Hexokinase-1 bound to mitochondria drives cardiac endothelial inflammation, a hallmark of heart failure and a preserved ejection fraction, and this heart failure phenotype is reportedly alleviated by inhibition of O-GlcNAcylation. 154 Increased O-GlcNAcylation produced by OGA downregulation has deleterious effects on left ventricular function following experimental myocardial infarction 155 and contributes to right ventricular dysfunction in experimental pulmonary hypertension.…”
Section: Autophagic Fluxmentioning
confidence: 99%